2018
DOI: 10.1021/acs.macromol.8b00845
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Responsive Hyperbranched Poly(ionic liquid)s: Assembly and Phase Transformations

Abstract: A library of linear and branched amphiphilic poly­(ionic liquid)­s based on hydrophobic cores and peripheral thermally sensitive shells was synthesized and studied with regard to their ability to form stimuli-responsive, organized assemblies in aqueous media. The thermally responsive derivatives of poly­(ionic liquid)­s were synthesized by neutralizing 32 terminal carboxyl groups of functionalized polyester cores by amine-terminated poly­(N-isopropyl­acrylamide)­s (PNIPAM) (50% and 100%). We observed that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 78 publications
(202 reference statements)
2
27
0
3
Order By: Relevance
“…20 In a recent advance and as a rare example of thermoresponsive PILs with highly branched architecture, Tsukruk et al tailored core/shell polymers composed of hyperbranched carboxylate-functionalized polyester cores and ammonium-terminated poly(N-isopropylacrylamide) (PNIPAM) chains bonded to the core molecules as thermoresponsive corona by ionic interactions. 21 In the past, hyperbranched polymer ionic liquids (hyperPILs) with onion-like compartmentalized topology have been developed in our group, which combine the features of PIL materials with the benefits of unimolecular micellar architecture. 22 They are composed of a hyperbranched poly(3-ethyl-3-hydroxymethyloxetane) (PEHO) core, an inner ionic shell of covalently attached imidazolium cations with tosylate counter anions, and a non-polar outer shell of alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
“…20 In a recent advance and as a rare example of thermoresponsive PILs with highly branched architecture, Tsukruk et al tailored core/shell polymers composed of hyperbranched carboxylate-functionalized polyester cores and ammonium-terminated poly(N-isopropylacrylamide) (PNIPAM) chains bonded to the core molecules as thermoresponsive corona by ionic interactions. 21 In the past, hyperbranched polymer ionic liquids (hyperPILs) with onion-like compartmentalized topology have been developed in our group, which combine the features of PIL materials with the benefits of unimolecular micellar architecture. 22 They are composed of a hyperbranched poly(3-ethyl-3-hydroxymethyloxetane) (PEHO) core, an inner ionic shell of covalently attached imidazolium cations with tosylate counter anions, and a non-polar outer shell of alkyl chains.…”
Section: Introductionmentioning
confidence: 99%
“…PNIPAM features a near body lower critical solution temperature (LCST = 32°C) and biocompatibility, and is thus very appealing for biomedical applications. [32][33][34][35][36] So far the reports mentioning both PVDF and PNIPAM only describe polymer blends for the preparation of electrospun fibers or flat membranes, or the grafting of PNIPAM on PVDF membranes. 37 To date, the preparation of PNIPAM-b-PVDF block copolymers (BCPs) and the study of their self-assembly in selective solvents have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[98] For example, a library of linear and branched amphiphilic poly(ionic liquid)s based on hydrophobic cores and peripheral thermally sensitive shells has been developed ( Figure 17A). [99] As shown in Figure 18, the thermally responsive derivatives of poly(ionic liquid)s were synthesized by neutralizing 32 terminal carboxyl groups of functionalized polyester cores by amine-terminated poly(N-isopropylacrylamide)s. The obtained PILs exhibited unique thermally triggered assembly behavior with morphologies by a combination of chemical and thermal stimuli; that is, the PILs formed spherical micellar assemblies with diverse morphologies, such as micelles and their aggregates, depending on the terminal compositions with reduced sizes for hyperbranched PILs. Increasing the temperature above lower critical solution temperature (LCST) led to form network-like aggregates, large vesicles, and spherical micelles ( Figure 17B).…”
Section: Il-based Thermo-responsive Materialsmentioning
confidence: 99%